Gas7 Is Required for Mesenchymal Stem Cell-Derived Bone Development - Chuck C.-K. Chao; Feng-Chun Hung; Jack J. Chao (Stem Cells International, 2013)
Mesenchymal stem cells (MSCs) can differentiate into osteoblasts and lead to bone formation in the body. Osteoblast differentiation and bone development are regulated by a network of molecular signals and transcription factors induced by several proteins, including BMP2, osterix, and Runx2. We recently observed that the growth-arrest-specific 7 gene (Gas7) is upregulated during differentiation of human MSCs into osteoblasts. Downregulation of Gas7 using short-hairpin RNA decreased the expression of Runx2, a master regulator of osteogenesis, and its target genes (alkaline phosphatase, type I collagen, osteocalcin, and osteopontin). In addition, knockdown of Gas7 decreased the mineralization of dexamethasone-treated MSCs in culture. Conversely, ectopic expression of Gas7 induced Runx2-dependent transcriptional activity and gene expression leading to osteoblast differentiation and matrix mineralization. Genetic mutations of the Gas7 gene increased body fat levels and decreased bone density in mice. These results showed that Gas7 plays a role in regulating the pathways which are essential for osteoblast differentiation and bone development. In this review, we summarize the involvement of Gas7 in MSC-based osteogenesis and osteoporosis and describe the possible mechanisms responsible for the maintenance of cellular homeostasis in MSCs and osteoblasts.